A Gramscian Study of Ideology and Hegemony in Amiri Baraka play: The Dutchman - Shiva Zaheri Birgani; Maryam Jafari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This paper attempts to investigate significations of the tropes of whiteness and blackness in white American culture in Baraka`s play, The Dutchman. . Gramsci is concerned with how one views man in history. His point is that men determine history rather than the reverse and this history is determined by the way in which men produce their means of subsistence. Man therefore is a social and “material” entity since. By producing their means of subsistence men are indirectly producing their actual material life.   Man’s ability to produce, the means of production, and the product produced, therefore, are central to man’s ability to be self-determined, to be real rather than an abstraction, a concept. It is in man’s reality, a reification brought about by the conscious act of production that he establishes his humanity. Marx’s humanism, therefore, is social in that man produces for more than himself; it is material in the “mode of production.” By material is not meant “psychic motivation” towards material goods. Based on the Gramsci hegemony, the black man has no history, he must create it; more importantly, since, according to Baraka, “Negro Literature” can never emerge from black consciousness unless it separates itself from the pre-established conditions, the literature must create and define itself in the process of becoming.